The rupture mechanism of rubredoxin is more complex than previously thought. Issue 23 (2nd June 2020) - Scheurer, Maximilian; Dreuw, Andreas; Head-Gordon, Martin; Stauch, Tim
Abstract : Using steered molecular dynamics simulations and strain analysis it is shown that, in contrast to previous assumptions, the experimentally found low rupture force of the iron–sulfur-bond in rubredoxin cannot be explained by hydrogen bond networks. Abstract : The surprisingly low rupture force and remarkable mechanical anisotropy of rubredoxin have been known for several years. Exploiting the first combination of steered molecular dynamics and the quantum chemical Judgement of Energy DIstribution (JEDI) analysis, the common belief that hydrogen bonds between neighboring amino acid backbones and the sulfur atoms of the central FeS4 unit in rubredoxin determine the low mechanical resistance of the protein is invalidated. The distribution of strain energy in the central part of rubredoxin is elucidated in real-time with unprecedented detail, giving important insights into the mechanical unfolding pathway of rubredoxin. While structural anisotropy as well as the contribution of angle bendings in the FeS4 unit have a significant influence on the mechanical properties of rubredoxin, these factors are insufficient to explain the experimentally observed low rupture force. Instead, the rupture mechanism of rubredoxin is far more complex than previously thought and requires more than just a hydrogen bond network.